Impact of sexual maturity on the welfare of immunocastrated v. entire heavy female pigs. (29th November 2017) - Di Martino, G.; Scollo, A.; Garbo, A.; Lega, F.; Stefani, A. L.; Vascellari, M.; Natale, A.; Zuliani, F.; Zanardello, C.; Tonon, F.; Bonfanti, L.
Abstract : During oestrus, fattening female pigs are more prone to lameness, fractures and wounds due to mounting and agonistic behaviours of penmates. This study assessed the effect of sexual maturity on the behaviour and welfare of heavy female pigs slaughtered at 36 weeks of age (180±10 kg) for dry-cured ham production. An immunocastrated control group was used for comparison. In all, 56 15-week-old female pigs, individually identifiable by back tattoos were equally distributed among four pens. All animals from two pens were subject to a three-dose immunocastration schedule at 16, 20 and 32 weeks of age. Skin lesions and behaviours were assessed at 18, 23, 28, 33 and 36 weeks of age. A blood sample was collected at 20, 24, 28 and 32 weeks of age for assessing health/stress parameters and GnRH antibodies. At slaughter, ovaries were weighed, measured and histologically examined; stomachs, carcasses and lungs were scored for lesions and a further blood sample was taken. Immunocastrated pigs did not significantly differ from controls in growth rate, feed efficiency and slaughter performances (lung score, gastric score, backfat thickness). However, they showed a lower frequency of aggressive interactions at 33 and 36 weeks, lower front lesions at 28 weeks, but higher at 30 weeks; a lower haptoglobin level at 28 weeks, a lower level of cortisol and back lesions at slaughter (36 weeks). These findings suggest a low, yet not negligible, impact of sexual maturity on the welfare of heavy female pigs.